Merapi Volcano Refugee Management Information System - Saputro, Muhammad Ikhwan Maulana; Anggara, Afwan (Kirana Publisher (KNPub), 2025)
The Mount Merapi Refugee Management Information System is a system designed to provide information related to the evacuation process in emergencies or disaster situations. The main purpose of this system is to assist and ensure safety and efficiency in the evacuation process. This system can include various elements, such as emergency monitoring, early warning, evacuation plans, evacuation routes, barracks capacity, rescue team coordination, and the latest information for the affected communities. This system is used to optimize the evacuation process of residents when Mount Merapi erupts. By utilizing communication technology, this system provides real-time information on volcanic activity developments, determines evacuation zones in the Merapi disaster area, and provides guidance and notifications to communities around Mount Merapi through various communication channels. The integration of geospatial data and mapping enables the identification of the best evacuation routes, while a user-friendly interface facilitates access and interaction for users. This system is expected to improve evacuation efficiency, minimize risks, and enhance the safety of communities in areas affected by Mount Merapi disasters. The Evacuation Information System is expected to improve coordination, rapid response, and community safety in dealing with emergency situations.